Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture: Project highlights - Vernooy, Ronnie (2019)
This brief presents highlights of the project "Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture", which was coordinated by Bioversity International, under the framework of the Food and Agriculture Organization of the United Nations/Treaty Secretariat/Bioversity International Joint Capacity Building Programme for Developing Countries on the Implementation of the Treaty and its Multilateral System (MLS). The project, which ran from 2012 -2016, aimed to: promote the participation of countries in the multilateral system of access and benefit-sharing of the Treaty; identify means to improve countries’ access to plant genetic resources for food and agriculture; and pursue options to benefit from other aspects of the Treaty.